Collective action for innovation and small farmer market access: The Papa Andina experience - Devaux, André; Velasco, Claudio; López, Gastón; Bernet, Thomas; Ordinola, Miguel; Pico, Hernán; Thiele, Graham; Horton, Douglas E. (International Food Policy Research Institute, 2007)
The Andean highlands are home to some of the poorest rural households in South America. Native potato varieties and local knowledge for their cultivation and use are unique resources possessed by farmers in these areas. As the forces of globalization and market integration penetrate the Andes, they present both challenges and opportunities for farmers there. This paper reports on how the Papa Andina Regional Initiative is promoting the use of collective action to reduce poverty in the Andes, by developing market niches and adding value to potatoes, particularly the native potatoes grown by poor farmers. Since 1998, Papa Andina has worked with partners in Bolivia, Ecuador and Peru to stimulate pro-poor innovation within market chains for potato-based products. Market chain actors (including small-scale potato producers, traders, and processors), researchers, and other service providers have engaged in innovation processes via two principal tools for facilitating collective action: the Participatory Market Chain Approach (PMCA) and Stakeholder Platforms. The PMCA fosters commercial, technological, and institutional innovation through a structured process that builds interest, trust, and collaboration among participants. Stakeholder Platforms provide a space for potato producers, other market chain actors, and service providers to come together to identify their common interests, share knowledge, and develop joint activities. The PMCA and Stakeholder Platforms have empowered Andean potato farmers by expanding their knowledge of markets, market agents, and business opportunities. Social networks built up among producers, market agents, and service providers have stimulated commercial innovation, which in turn has stimulated technical and institutional innovation. These innovations have allowed small farmers to market their potatoes on more favorable terms and other market chain actors to increase their incomes. This paper describes experiences with collective action in Bolivia, Ecuador, and Peru, via the PMCA and Stakeholder Platforms. Based on these experiences, a number of lessons are formulated for using collective action to stimulate innovation, market access, and poverty reduction in other settings.